2021
DOI: 10.3390/jcm10051147
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical Diagnosis of Acromegaly

Abstract: Background: The diagnosis of acromegaly still poses a clinical challenge, and prolonged diagnostic delay is common. The most important assays for the biochemical diagnosis and management of acromegaly are growth hormone (GH) and insulin-like growth factor-1 (IGF-1). Objective: Discuss the role of IGF-1, basal serum GH, and nadir GH after oral glucose tolerance test (OGTT) for the diagnosis, management, and treatment of patients with acromegaly. Methods: We performed a narrative review of the published data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 43 publications
1
24
0
3
Order By: Relevance
“…Although NLR, PLR, and SII values were significantly higher in acromegaly than in NFPAs, these inflammatory indices cannot be used to discriminate GH-secreting pituitary tumors from NFPAs due to very low diagnostic accuracy. A ROC curve analysis confirmed that traditional markers of acromegaly, such as GH/IGF-1 showed the best sensitivity and specificity ranged from 92-100% and 89-100% respectively, which is consistent with literature data [4].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although NLR, PLR, and SII values were significantly higher in acromegaly than in NFPAs, these inflammatory indices cannot be used to discriminate GH-secreting pituitary tumors from NFPAs due to very low diagnostic accuracy. A ROC curve analysis confirmed that traditional markers of acromegaly, such as GH/IGF-1 showed the best sensitivity and specificity ranged from 92-100% and 89-100% respectively, which is consistent with literature data [4].…”
Section: Discussionsupporting
confidence: 89%
“…GH-secreting pituitary tumors are characterized by a benign nature and follow an indolent course [1]. Initially, the clinical features of acromegaly may be very subtle, which most likely results in a prolonged diagnostic delay of an average of 5 to 10 years after the onset of first signs and symptoms [4]. It is well established that long-lasting GH/IGF-1 axis hypersecretion leads to a number of systemic complications, especially increased risk of cardiovascular diseases that reduce the patient's quality of life and survival [5].…”
Section: Introductionmentioning
confidence: 99%
“…acromegaly). After an oral glucose tolerance test of 75 mg GH suppressed to a nadir GH of 0.73 μg/L, above the level suggested by some authors as a sensitive value to diagnose acromegaly (GH nadir of <0.4 μg/L ( 2 )) but below the level suggested by the 2014 Endocrine Society Clinical Practice Guidelines of GH nadir of <1 μg/L ( 3 ).…”
Section: Investigationmentioning
confidence: 74%
“…Our patient's presentation of headache may be multifactorial including a possible initial pituitary adenoma, an ES, or directly from an elevated GH level. Ectopic acromegaly occurs due to the secretion of GHRH or rarely GH from extra-pituitary tumors (24). When compared to a pituitary cause of acromegaly where GHRH levels may be normal or more often suppressed, in the case of ectopic GHRH secretion, serum GHRH levels are raised (25,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic acromegaly occurs due to the secretion of GHRH or rarely GH from extra-pituitary tumors ( 24 ). When compared to a pituitary cause of acromegaly where GHRH levels may be normal or more often suppressed, in the case of ectopic GHRH secretion, serum GHRH levels are raised ( 25 , 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%